A framework to analyze capability and travel in formal and informal urban settings: A case from Mumbai. (December 2017) - Chikaraishi, Makoto; Jana, Arnab; Bardhan, Ronita; Varghese, Varun; Fujiwara, Akimasa
Abstract: This study analyzes the association between individual capabilities and travel time in Mumbai. We formulate a conceptual hypothesis by differentiating the production (e.g., commuting) aspects from the consumption (e.g., leisure) aspects of travel. We argue that less capable people may focus more on the production aspects, whereas more capable people may focus more on the consumption aspects. Two operationalized hypotheses are introduced for empirical verification: (1) travel time is significantly related to individual capability and is shorter for less capable people, and (2) the variance of travel time, indicating the degree of freedom of movement, has a positive association with individual capability. To confirm the hypotheses empirically, an activity–travel survey was conducted in middle-income group housing, slums, and slum rehabilitation units in Mumbai, India. Our results support both hypotheses, suggesting that, when people are less capable, they attach more importance to the production aspects of travel, but as capability increases, the consumption aspects become more vital. Based on our findings, we discuss practical implications for transport appraisal in the development context. Highlights: Offers a frameworks of the association between personal capability and travel behavior. Empirically confirms the association by using an activity-travel survey in Mumbai. Explores the association is important for achieving the inclusivity of the city. The travel time saving might underestimate the benefits for less capable people.